Knowledge as a Predictor of Insurance Coverage Under the Affordable Care Act. Issue 4 (April 2017) - Hoerl, Maximiliane; Wuppermann, Amelie; Barcellos, Silvia H.; Bauhoff, Sebastian; Winter, Joachim K.; Carman, Katherine G.
Abstract : Background: The Affordable Care Act established policy mechanisms to increase health insurance coverage in the United States. While insurance coverage has increased, 10%–15% of the US population remains uninsured. Objectives: To assess whether health insurance literacy and financial literacy predict being uninsured, covered by Medicaid, or covered by Marketplace insurance, holding demographic characteristics, attitudes toward risk, and political affiliation constant. Research Design: Analysis of longitudinal data from fall 2013 and spring 2015 including financial and health insurance literacy and key covariates collected in 2013. Subjects: A total of 2742 US residents ages 18–64, 525 uninsured in fall 2013, participating in the RAND American Life Panel, a nationally representative internet panel. Measures: Self-reported health insurance status and type as of spring 2015. Results: Among the uninsured in 2013, higher financial and health insurance literacy were associated with greater probability of being insured in 2015. For a typical uninsured individual in 2013, the probability of being insured in 2015 was 8.3 percentage points higher with high compared with low financial literacy, and 9.2 percentage points higher with high compared with low health insurance literacy. For the general population, those with high financial and health insurance literacy were more likely to obtain insurance through Medicaid or the Marketplaces compared with being uninsured. The magnitude of coefficients for these predictors was similar to that of commonly used demographic covariates. Conclusions: A lack of understanding about health insurance concepts and financial illiteracy predict who remains uninsured. Outreach and consumer-education programs should consider these characteristics. Abstract : Supplemental Digital Content is available in the text.